Identification of enzymatic genes with the potential to reduce biomass recalcitrance through lignin manipulation in Arabidopsis - Shingo Sakamoto; Naofumi Kamimura; Yosuke Tokue; Miyuki T. Nakata; Masanobu Yamamoto; Shi Hu; Eiji Masai; Nobutaka Mitsuda; Shinya Kajita (Biotechnology for Biofuels, 2020)
Abstract Background During the chemical and biochemical decomposition of lignocellulosic biomasses, lignin is highly recalcitrant. Genetic transformation of plants to qualitatively and/or quantitatively modify lignin may reduce these recalcitrant properties. Efficient discovery of genes to achieve lignin manipulation is thus required. Results To screen for new genes to reduce lignin recalcitrance, we heterologously expressed 50 enzymatic genes under the control of a cinnamate 4-hydroxylase (C4H) gene promoter, derived from a hybrid aspen, which is preferentially active in tissues with lignified cell walls in Arabidopsis plants. These genes encode enzymes that act on metabolites in shikimate, general phenylpropanoid, flavonoid, or monolignol biosynthetic pathways. Among these genes, 30, 18, and 2 originated from plants, bacteria, and fungi, respectively. In our first screening step, 296 independent transgenic plants (T1 generation) harboring single or multiple transgenes were generated from pools of seven Agrobacterium strains used for conventional floral-dip transformation. Wiesner and Mäule staining patterns in the stems of the resultant plants revealed seven and nine plants with apparent abnormalities in the two respective staining analyses. According to genomic PCR and subsequent direct sequencing, each of these 16 plants possessed a gene encoding either coniferaldehyde dehydrogenase (calB), feruloyl-CoA 6′-hydroxylase (F6H1), hydroxycinnamoyl-CoA hydratase/lyase (couA), or ferulate 5-hydroxylase (F5H), with one transgenic plant carrying both calB and F6H1. The effects of these genes on lignin manipulation were confirmed in individually re-created T1 transgenic Arabidopsis plants. While no difference in lignin content was detected in the transgenic lines compared with the wild type, lignin monomeric composition was changed in the transgenic lines. The observed compositional change in the transgenic plants carrying calB, couA, and F5H led to improved sugar release from cell walls after alkaline pretreatment. Conclusions Simple colorimetric characterization of stem lignin is useful for simultaneous screening of many genes with the potential to reduce lignin recalcitrance. In addition to F5H, the positive control, we identified three enzyme-coding genes that can function as genetic tools for lignin manipulation. Two of these genes (calB and couA) accelerate sugar release from transgenic lignocelluloses.